«Social responsibility of sociology: current challenges» («round table» within the framework of ХІХ International scientific conference «Kharkiv sociological readings») - Соціологічна асоціація України, САУ; Харківський національний университет імені В.Н. Каразіна, ХНУ імені В.Н. Каразіна (Ukrainian Sociological Journal, 2017)
Round table «Social responsibility of sociology: current challenges» was conducted on 5th of November 2015 within the framework of ХІХ International scientific conference «Kharkiv sociological readings». The round table was organised by Sociological association of Ukraine and Sociological department of V.N. Karazin Kharkiv national university. Participants of round table are represented by leading sociologists of Ukraine, PhD students, students, principals of sociological service organisations, journalists. The main focus of discussion was the questions of social responsibility of sociology in contemporary world, professional solidarity of sociologists, academical freedom and freedom of speech in general. Texts of talks are giving in the original languages.